Endoscopic Ultrasonography Can Prevent Unnecessary Diagnostic Endoscopic Retrograde Cholangiopancreatography Even in Patients with High Likelihood of Choledocholithiasis and Inconclusive Ultrasonography: Results of a Prospective Study - Ruchir Patel; Meghraj Ingle; Dhaval Choksi; Prateik Poddar; Vikas Pandey; Prabha Sawant (Korean Society of Gastrointestinal Endoscopy, 2017)
Background/Aims Endoscopic retrograde cholangiopancreatography (ERCP) is the initial therapy recommended for patients with high likelihood of choledocholithiasis. To determine whether endoscopic ultrasonography (EUS) can prevent diagnostic ERCPs in patients with high probability of choledocholithiasis and inconclusive ultrasonography (US). Methods All patients with high likelihood of choledocholithiasis and negative US underwent EUS. ERCP was performed for the patients who showed a definite stone/sludge on EUS. Patients without choledocholithiasis were followed up for 3 months. The primary outcome was avoidance of diagnostic ERCP. Results We included 78 patients (51 women; 27 men). Of these, 25 and 7 (total 41%) were diagnosed with choledocholithiasis and sludge, respectively; stone/sludge was removed in 96.9% of the patients. EUS ruled out choledocholithiasis in 38 patients (48.7%). Two of them were found to have choledocholithiasis on follow-up. The sensitivity, specificity, positive and negative predictive value of EUS for detecting choledocholithiasis were 93.9%, 97.3%, 96.9%, and 94.7%, respectively. Unnecessary ERCP was avoided in 57.7% of the patients by using the EUS-first approach. Conclusions EUS is a highly accurate and safe procedure. EUS can replace ERCP as the initial investigation in patients with a high probability of choledocholithiasis. It avoids unnecessary ERCP; hence, decreasing related costs and complications.